Application of numerical simulation for the modernization of the exhaust system of gas turbine engines - T. V. Boshchenko; S. Yu. Lebedev; A. N. Korolevskikh (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is to modernize the design of the exhaust system of gas turbine engines (GTE) in order to reduce aerodynamic losses using numerical methods (CFD methods) for simulating the flow of exhaust gases.Method. The directions of modernization were chosen by considering the pattern of the flow of exhaust gases (separated flow zones and vortex flows) in the exhaust system during numerical modeling (Computational Fluid Dynamics). The modernization of the exhaust system consists in profiling the axial diffuser and changing the design of the gas collector.Result. The profiling of the axial diffuser was performed using numerical simulation methods. The design of the gas collector was changed based on the technical solution proposed by V.B. Yavkin. Numerical simulation of the flow of exhaust gases in the modernized exhaust device was performed. To evaluate the results of modernization in numerical models of the modernized design and prototype, the values of aerodynamic losses at the outlet of the axial diffuser and gas collector were determined.Conclusion. CFD modeling made it possible to obtain data on the structure of the exhaust gas flow in the upgraded exhaust system, to see the pattern of the distribution of velocities and pressures. The results of the numerical experiment showed a decrease in pressure losses in the exhaust system by 11% relative to the prototype.